Rehabilitation of degraded land in India through community-based initiatives - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Employs participatory approach to rehabilitate common property resources by developing biodiesel plantations through 1) consortium approach among govt. line departments, NGOs, CBOs, and ICRISAT; and 2) collective action